2018
DOI: 10.2147/ott.s160196
|View full text |Cite
|
Sign up to set email alerts
|

High expression of COL10A1 is associated with poor prognosis in colorectal cancer

Abstract: BackgroundHigh expression of collagen type X alpha 1 chain (COL10A1), a member of the collagen family, had been observed in various human cancers, but the detailed function and molecular mechanism of COL10A1 were largely unclear.AimThe aim of this study was to investigate the expression of COL10A1 in colorectal cancer (CRC) tissues and cells and to reveal its biological function and mechanism in CRC.Materials and methodsImmunohistochemistry (IHC), real-time quantitative polymerase chain reaction (QPCR) and Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 28 publications
5
51
0
Order By: Relevance
“…Collagen type X alpha 1 (COL10A1), a secreted, short-chain collagen, belongs to the collagen family, which is a major interstitial matrix component [5]. COL10A1 expression is elevated in many solid tumor types, such as colon cancer, esophagus cancer, and breast cancer, and displays vital roles in many critical cellular processes such as cell proliferation, migration, invasion and tumor vasculature [6][7][8]. COL10A1 protein levels in plasma might be a potential diagnostic predictor for early breast cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Collagen type X alpha 1 (COL10A1), a secreted, short-chain collagen, belongs to the collagen family, which is a major interstitial matrix component [5]. COL10A1 expression is elevated in many solid tumor types, such as colon cancer, esophagus cancer, and breast cancer, and displays vital roles in many critical cellular processes such as cell proliferation, migration, invasion and tumor vasculature [6][7][8]. COL10A1 protein levels in plasma might be a potential diagnostic predictor for early breast cancer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have analyzed the differential gene expression profiles of normal and neoplastic tissue of different cancers and identified a set of genes including COL10A1 16 18 . Overexpression of COL10A1 protein levels correlates with colon cancer 19 , 20 . However, the pathophysiological role and relevance of COL10A1 to GC invasion and metastasis remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, COL10A1 is highly expressed in several types of human tumors, while it exists at a lower level in normal tissues [14,15]. Studies on COL10A1 and colorectal cancer have proved that high expression of COL10A1 is an independent risk factor for prognosis and overall survival rates in patients with colorectal cancer [16]. In this study, we identified COL10A1 as an NSCLC-associated gene by screening it through the bioinformatics databases and miR-384 down-regulated COL10A1 by targetting it.…”
Section: Introductionmentioning
confidence: 99%